2019
DOI: 10.24251/hicss.2019.170
|View full text |Cite
|
Sign up to set email alerts
|

Customer Responses to Service Robots – Comparing Human-Robot Interaction with Human-Human Interaction

Abstract: This paper investigates how service failures affect customers by comparing human-robot interactions with human-human interactions. More specifically, it compares customers' satisfaction in a service robot interaction depending on a service failure with the customers' satisfaction in a frontline service employee interaction. On a theoretical basis, extant literature on the uncanny valley paradigm proposed that service robots would create lower satisfaction than human frontline employees would. However, I find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…Research on robotic service failure is scant since much effort has been spent on examining the functions, design and acceptance of service robots. In an experimental laboratory study, Merkle (2019) found that contradictory to his theoretical reasoning based on uncanny valley paradigm (Mori, 1970) which assumes that if a robots become too humanoid, people perceive this experience as creepy and unpleasantand attribution theory; customers indicated a higher level of satisfaction when they experienced a service failure caused by a robot than when they encountered a failure by a frontline service employee. In Merkle's (2019) study, customers attributed the service failure to external circumstances because they perceived it to be beyond the control of the robots.…”
Section: Service Customersmentioning
confidence: 97%
“…Research on robotic service failure is scant since much effort has been spent on examining the functions, design and acceptance of service robots. In an experimental laboratory study, Merkle (2019) found that contradictory to his theoretical reasoning based on uncanny valley paradigm (Mori, 1970) which assumes that if a robots become too humanoid, people perceive this experience as creepy and unpleasantand attribution theory; customers indicated a higher level of satisfaction when they experienced a service failure caused by a robot than when they encountered a failure by a frontline service employee. In Merkle's (2019) study, customers attributed the service failure to external circumstances because they perceived it to be beyond the control of the robots.…”
Section: Service Customersmentioning
confidence: 97%
“…Existing research shows that the theory is suitable to understand responsibility attribution of users towards new AI-based technology [14,41]. Previous studies in HRI have examined attributional thoughts in the context of different service outcomes like failure vs. success [4], with different frontline agents oftentimes robot vs. human [4,12,14], technology's autonomy and behavioral control [16], different user attributions like robot or organization responsibility [14] and relative status of the robot [41].…”
Section: Responsibility Attributionmentioning
confidence: 99%
“…In robotics anthropomorphic design is used to facilitate HRI, since user acceptance of robots, as well as the effectiveness of HRI, are influenced by attributing social behavior and presence to robots (e.g., through the use of facial expressions or a human-like physical design of the robot) [25,26]. Yet, despite this trend in robotic research to design and develop robots (e.g., service robots) which are increasingly human-like, studies suppose that customer satisfaction is higher within a pure human-human interaction as opposed to an HRI [6,20]. The uncanny valley paradigm further predicts a positive relationship between a robot's human-likeness and the robot's likability by the human [3,20,27].…”
Section: Physical Designmentioning
confidence: 99%
“…The COVID-19 pandemic significantly influenced the observed growing importance of the service sector within the last decades, leading to an acceleration of technological developments and hence, the increased use of autonomous and intelligent service robots [1][2][3][4]. This can be experienced in everybody's daily life, where technologies have already penetrated several areas [3][4][5], e.g., customers interact with airport self-service kiosks, internet-based services, and automated teller machines [6]. Especially, service robots offer useful perspectives and can assist humans by providing several advising and informing services for customers in numerous areas, e.g., banking, education, health, hospitality, and retail [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation